Studied on Thermal Decomposition Kinetics of 3-Methyl-4-nitroso-5-pyrazolone Complexes with Thorium(IV) and Dioxouranium(IV) Nitrate - Arora, Kishor (Asian Journal of Chemistry, 2010)
Parameters related to thermal decomposition kinetics, viz., E*, A and ΔS* are computed on the basis of thennal decomposition data on the complexes of 3-mcthyl-4-nitroso-5-pyrazolone with thorium(IV) and dioxouranium(VI) nitrate using different methods and it was inferred that the values of E* are sufficiently high and positive while ΔS* are negative.